The RNA‐binding protein LARP4 regulates cancer cell migration and invasion. Issue 11 (26th September 2016) - Seetharaman, Shailaja; Flemyng, Ella; Shen, Jiazhen; Conte, Maria R.; Ridley, Anne J.
Abstract : LARP4 is a La‐related RNA‐binding protein implicated in regulating mRNA translation, which interacts with poly(A)‐binding protein (PABP). We previously identified LARP4 in an RNAi screen as one of several genes that regulate the shape of PC3 prostate cancer cells. Here we show that LARP4 depletion induces cell elongation in PC3 cells and MDA‐MB‐231 breast cancer cells. LARP4 depletion increases cell migration and invasion, as well as inducing invasive cell protrusions in 3D Matrigel. Conversely, LARP4 over‐expression reduces cell elongation and increases cell circularity. LARP4 mutations are found in a variety of cancers. Introduction of some of these cancer‐associated mutations, including a truncation mutant, into LARP4 enhances its effects on cell morphology. The truncation mutant shows enhanced interaction with PABP. We propose that LARP4 inhibits migration and invasion of cancer cells, and that some cancer‐associated mutations stimulate these effects of LARP4. © 2016 The Authors. Cytoskeleton Published by Wiley Periodicals, Inc.